Kinesin-12 POK2 polarization is a prerequisite for a fully functional division site and aids cell plate positioning - Livanos, Panteleimon; Kriechbaum, Choy; Remers, Sophia; Herrmann, Arvid; Müller, Sabine (Nature Communications, 2025)
Division plane positioning in plants relies on the remarkably accurate selection of the cortical division zone (CDZ), earmarked by the preprophase band of microtubules. The PHRAGMOPLAST ORIENTING KINESIN 1 and 2 (POK1/2) play pivotal roles in CDZ maintenance in mitosis and guide the approaching phragmoplast during cytokinesis. Our knowledge regarding the mechanism of POK recruitment and subsequent maintenance is hitherto limited. Here, we report that POK2 arrives at the preprophase band utilizing a secondary microtubule-binding site within its carboxy-terminus. Effective tethering to the plasma membrane is achieved through non-specific electrostatic interactions with phospholipids. Reaching the cortex via premitotic cortical microtubules emerges as a prerequisite for POK2 polarization, as the order and the density of prophase microtubules become particularly relevant in the preprophase band-compromised mutant trm678. POK2 binding to cortical microtubules templates its future position at the cortex and appears critical for adequate division site setup and consequently tissue architecture.
CRIS-Team Scopus Importer:2025-05-23
Keywords: cell division; preprophase band; microtubules; phragmoplast; kinesin; phospholipids; Arabidopsis

N-terminal domain of ARF-GEF GNOM prevents heterodimerization with functionally divergent GNL1 in Arabidopsis - Brumm, Sabine; Singh, Manoj K.; Kriechbaum, Choy; Richter, Sandra; Huhn, Kerstin; Kucera, Tim; Baumann, Sarah; Wolters, Hanno; Takada, Shinobu; Juergens, Gerd (Plant Journal, 2022)
Evolutionary change following gene duplication can lead to functionally divergent paralogous proteins. If comprising identical subunits their random assortment would also form potentially detrimental heteromeric proteins. In Arabidopsis, the ARF GTPase guanine-nucleotide exchange factor GNOM is essential for polar recycling of auxin-efflux transporter PIN1 from endosomes to the basal plasma membrane whereas its paralog GNL1 mediates retrograde Golgi-endoplasmic reticulum traffic. Here we show that both GNOM and GNL1 form homodimers but no heterodimers. To assess the biological significance of this, we generated transgenic plants expressing engineered heterodimer-compatible GNOM variants. Those plants showed developmental defects such as the failure to produce lateral roots. To identify mechanisms underlying heterodimer prevention, we analyzed interactions of the N-terminal dimerization and cyclophilin-binding (DCB) domain. Each DCB domain interacted with the complementary fragment (ΔDCB) both of their own and of the paralogous protein. However, only DCBGNOM interacted with itself whereas DCBGNL1 failed to interact with itself and with DCBGNOM. GNOM variants in which the DCB domain was removed or replaced by DCBGNL1 revealed a role for DCB-DCB interaction in the prevention of GNOM-GNL1 heterodimers whereas DCB-ΔDCB interaction was essential for dimer formation and GNOM function. Our data suggest a model of early DCB-DCB interaction that facilitates GNOM homodimer formation, indirectly precluding formation of detrimental heterodimers.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Arabidopsis; ARF-GEF paralogs; DCB domain; domain interaction; heterodimer prevention; homodimers

On the edge — how plant cells monitor growth - Kriechbaum, Choy; Müller, Sabine (Nature Plants, 2024)
Cell edges are part of a coordinate system used by the cell to direct three-dimensional growth in an organized manner. They emerge as signalling hubs with unique composition, capable of sensing mechanical stresses derived from neighbouring cells, to negotiate and harmonize individual cellular growth rates, therefore avoiding mechanical conflict.
CRIS-Team Scopus Importer:2024-03-15

Plasma membrane and cytoplasmic compartmentalization: A dynamic structural framework required for pollen tube tip growth - Fritz, Carolin; Reimann, Theresa; Adler, Jeremy; Knab, Johanna; Schulmeister, Sylwia; Kriechbaum, Choy; Müller, Sabine; Parmryd, Ingela; Kost, Benedikt (Plant Physiology, 2024)
Rapid, unidirectional pollen tube tip growth is essential for fertilization and widely employed as a model of polar cell expansion, a process crucial for plant morphogenesis. Different proteins and lipids with key functions in the control of polar cell expansion are associated with distinct domains of the plasma membrane (PM) at the pollen tube tip. These domains need to be dynamically maintained during tip growth, which depends on massive secretory and endocytic membrane trafficking. Very little is currently known about the molecular and cellular mechanisms responsible for the compartmentalization of the pollen tube PM. To provide a reliable structural framework for the further characterization of these mechanisms, an integrated quantitative map was compiled of the relative positions in normally growing Nicotiana tabacum (tobacco) pollen tubes of PM domains (i) enriched in key signaling proteins or lipids, (ii) displaying high membrane order, or (iii) in contact with cytoplasmic structures playing important roles in apical membrane trafficking. Previously identified secretory and endocytic PM domains were also included in this map. Internalization of regulatory proteins or lipids associated with PM regions overlapping with the lateral endocytic domain was assessed based on brefeldin A treatment. These analyses revealed remarkable aspects of the structural organization of tobacco pollen tube tips, which (i) enhance our understanding of cellular and regulatory processes underlying tip growth and (ii) highlight important areas of future research.
Created from Fastlane, Scopus look-up